Fixed point theorems for hybrid contraction without continuity - Gairola, U. C.; Krishan, Ram (Global Journal of Mathematical Analysis, 2015)
In this paper we establish a coincidence and fixed point theorems for hybrid contraction under generalized weakly contractive condition by using the concept of (IT)-commutativity in a complete metric space without appeal to continuity of mappings. Our results extend and generalize the results of Choudhury et al. [6] and others.